Climate Change and Geographic Ranges: The Implications for Russian Forests - Noce, Sergio; Caporaso, Luca; Santini, Monia (Frontiers in Ecology and Evolution, 2019)
Forest ecosystems of the Russian Federation are expected to face high risks under environmental dynamics related to climate change. Analyzing the likely impacts of climate change on forest ecosystems becomes crucial to understand the potential adaptation of forests, to guide management strategies, as well as to preserve their ecosystem services. With the aim to provide information on the possible modifications of geographic ranges, on the medium to long term, for some Russian dominant forest species under climate change, we applied a Cascade Ensemble System (CES) approach. This consists in combining an Ensemble Platform for Species Distribution Models (SDMs) to six bias-corrected Earth System Model (ESM) projections, in turn driven by two Representative Concentration Pathways (RCPs) proxy of greenhouse gas emission scenarios, in order to obtain maps of future suitability for forest species. The suitability information is then flagged with information about its ”likelihood”, adopting the IPCC terminology based on consensus among projections. Maps of aggregated changes were created in order to identify areas potentially more vulnerable to climate change. Results show that possible impacts of climate change (either gain or loss) were diversified across species with a pronounced Northward shift of the ranges. Further analyses were performed at sub-regional level revealing the potential for the Arctic Circle to become a refuge area for some conifer species. Species-aggregated change analyses spotted two distinct areas as more vulnerable to habitat change, in the central and south-east portions of Russian territory. Our findings represent useful and immediate biogeographical information available to Russian policy makers for delineating conservation strategies and forest management plans.